Characteristics, Impact, and Trends of Healthcare Simulation in Latin America and the Caribbean: A Bibliometric Analysis - Velásquez-Rimachi, Victor; Cabanillas-Lazo, Miguel; Prialé-Zevallos, Alvaro; Dubreuil-Wakeham, Solange; Samaniego-Lara, Daniela; Runzer-Colmenares, Fernando M; Mayta-Tristán, Percy (Simulation in healthcare : journal of the Society for Medical Simulation, 2025)
This study highlights the growing significance of healthcare simulation in enhancing the quality and safety of patient care across Latin America and the Caribbean, by analyzing bibliometric trends and the impact of publications on simulation-based clinical training between 2012 and 2022. Leveraging the Scopus database and VOSviewer software for thesaurus interaction analysis, the research identified 610 documents, accumulating 4681 citations, thereby indicating a burgeoning interest in this field with notable publication spikes in 2017 and 2020. Brazil and the United States emerged as leading contributors, with a primary focus on "simulation training," "clinical competence," "medical education," and "education." The study observed an uptick in international collaboration, mirroring the increase in document count and citations. This bibliometric review underscores the emphasis on evaluating technical skills and clinical practices as prevailing areas of interest, highlighting Brazil's significant academic contributions, and suggesting a promising future for the implementation of clinical simulation in the region. The study advocates for continued scholarly output to align with global advancements in medical simulation, aiming to optimize patient outcomes.